"Follow the Fallopian tube": A technique to improve sonographic identification of ovaries in children. Issue 1 (21st August 2020) - Kitami, Masahiro; Aoki, Hidekazu; Saito, Mioko
Abstract: Ovary detection is the first step in confirming ovarian lesions. The daughter cyst sign is widely used for this purpose; however, it is not always applicable. Recent improvements in image resolution allow Fallopian tube delineation, which can serve as a guide to identify the ovary. This anatomical approach ("follow the Fallopian tube" technique) comprises three steps: (1) confirm the uterus; (2) follow the Fallopian tube; and (3) find the ovary. Other applications of this approach include the differentiation between nonovarian and ovarian masses and ruling out ovarian torsion and an auto‐amputated ovary.